Intraoperative glycaemic control and the effectiveness of myocardial reperfusion – initial reports - Marcinkiewicz, Anna; Ostrowski, Stanisław; Janowska, Elżbieta; Zwoliński, Radosław; Jaszewski, Ryszard (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2012)
Introduction: The proper reperfusion after CABG relies on many factors. Intraoperative hyperglycaemia is a state associated with a negative prognosis. The ischemic markers – creatine kinase (CK-MB) and troponin I (T hs ) – are the molecular indicators of the aorto-coronary by-pass procedure effectiveness. Aim of the study: The purpose of the study was to assess the influence of intraoperative insulin infusion on the myocardial reperfusion, without concerning the preoperative metabolic condition. Materials and methods : The study included 42 randomly chosen patients, operated on in the Cardiosurgical Clinic in Lodz in 2010-2011. There were patients with diabetes (19), non-diabetic patients (20) and those with impaired glucose tolerance (3). During the operation4-5 glycaemic measurements were conducted. The glycaemic level of 135 mg/dl (7.5 mmol/l) was the aim. After the surgery CK-MB and T hs were assessed. The analysis included glycaemia from the operative day, and ischaemic marker measurements from the operative day and the first postoperative day. It also involved the blood pressure, the kind and amount of used liquids and medicaments. Results: 52.38% (22) patients were grouped as normoglycaemic (glicaemia ≤ 135 mg/dl in all measurements or except one). In 23.81% (10) patients there was intraoperative insulin infusion applied. The comparison of the operative measurements of glycaemia and CK-MB from the operative and first postoperative day showed positive correlation. The highest levels were noted in the group with insulin infusion (mean 46.4 U/l). In all groups the glycaemic measurements were further increasing on the intensive care unit (ICU). In the case of troponin measurements there were also higher levels noted in the hyperglycaemic patients than in the normoglycaemic. Conclusions : Proper intraoperative glycaemia is one of the conditions of a good surgical revascularization effect. The intraoperative use of insulin is not necessarily protective for the myocardium.